(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This article explores the socio-philosophical aspects of the formation of musical thinking within the spiritual development of youth in Uzbekistan. It examines the historical evolution of Uzbek music and the impact of reforms in shaping national musical identity. Special attention is given to the contributions of both local and foreign musicologists—particularly from Europe and Russia—who influenced musical culture in Turkestan during the late 19th and early 20th centuries. The study also reflects on the role of artistic recognition, fame, and legacy in the context of cultural continuity and youth education.